Students’ Politeness Strategies in Messaging a Lecturer: A Discourse Analysis - Arsita, Resa; Susilawati, Endang; Riyanti, Dwi (Universitas Pamulang, 2025)
The purpose of this study is to investigate the politeness strategies used by students when communicating with a lecturer via WhatsApp messages. The researcher conducted this study using discourse analysis, with data obtained from 22 final-year students of the English Education Study Program at Universitas Tanjungpura Pontianak, in the form of screenshot messages. The messages were analyzed using referential analysis to examine each utterance. Based on the findings, the students mostly used a combination of positive politeness strategies and negative politeness strategies when messaging a lecturer. Each strategy served its own function; for example, positive politeness strategies were mostly found at the beginning of the message as a form of greeting, while negative politeness strategies were used to indirectly convey intentions and to soften requests. The results of the analysis showed that most students applied politeness strategies appropriately based on the context when communicating with the lecturer, but some still inappropriately used certain words and terms in their messages. Therefore, it is necessary for students to be more aware of appropriate language use, especially in written communication, in order to maintain effective communication and foster a good relationship with the lecturer.